Naqd al-Qirāʾāt ʿinda al-Mufassirin: Dirāsat Muqāranat linaqd al-Ṭabari wa al-Ṭūsi liriwāyati Ḥafṣ ʿan ʿĀṣim - Jalil, Abdul (UIN Sunan Kalijaga Yogyakarta, 2022)
This article attempts to highlight the critical position towards Ḥafṣ’ riwāya held by the Sunni exegete Abu Ja’far Muhammad bin Jarir al-Tabari (d. 310/923) and the Shi’ite Abu Ja’far Muhammad ibn al-Hasan al-Tusi (d. 460/1067), both of which had occupied special status in their respective communities. This article focuses on the verses which have variant readings. It compares the ways in which the two exegetes, in their books Jāmi’ al-Bayān fī Ta’wīl Āy al-Qur’ān and al-Tibyān fī Tafsīr al-Qur’ān, present and criticize the variant readings of which Ḥafṣ is infirād (isolated) in that no other imam (the transmitter for the riwāya) would read that part of the Quran the same way as Ḥafṣ did. Al-Ṭabari seems to be more clear and courageous in criticizing Ḥafṣ’ riwāya, compared to al-Ṭūsī. In several cases the former did not consider the riwāya reliable on the basis of the violation of the ijma’ (consensus) of ulama or it being unfamiliar to him (by expressing lā qāri’ qara’ kaẓālik, “no one reads it that way”). On the other hand, al-Ṭūsī contented with exploring linguistic and syntax reasons for upholding the riwaya. In no case would he question the authority of al-qirā’āt al-sab’a (the seven variant readings of the Quran). This might be due to their status as being pre-Ibn-Mujāhid (al-Ṭabarī) and post- (al-Ṭūsī). However, the two exegetes did not base their tafsir on merely one but rather on a number of qirā’at. Thus this paper suggests that Ḥafṣ’ riwāya, particularly among exegetes, was not considered the highest in rank and most prolific as it is now.